Topical NAVS naphthalan for the treatment of oral lichen planus and recurrent aphthous stomatitis: A double blind, randomized, parallel group study - Rogulj, Ana Andabak (PLoS One, 2021)
AIM: To evaluate the effectiveness of non-aromatic very rich in steranes (NAVS) naphthalan in the treatment of oral lichen planus (OLP) and recurrent aphthous stomatitis (RAS). Null hypothesis was that there would be no difference between NAVS and topical steroids in the treatment of OLP and RAS. METHODS: The study consisted of two sub-trials conducted as randomized, double-blind controlled studies: first included OLP patients and second patients with RAS. Patients received either NAVS or 0.05% betamethasone dipropionate. Primary outcomes were activity score (OLP patients), No of lesions and lesion diameter (RAS patients) and pain intensity (VAS) while secondary outcome included the impact of the disease on quality of life assessed by Oral health impact profile (OHIP 14). RESULTS: No significant differences in terms of OLP clinical signs (p = 0.84, η(2) = 0.001) and responses on the OHIP-14 (p = 0.81, η(2) = 0.002) or on VAS (p = 0.14, η(2) = 0.079) between NAVS and betamethasone groups were observed. In RAS patients, no significant differences between the groups in terms of lesion number (at days 3 and 5, p = 0.33 and p = 0.98, respectively), lesion diameter (days 3 and 5, p = 0.24 and p = 0.84, respectively) were observed. However, in NAVS group a significant reduction of lesions diameter was observed on the 3(rd) day, while in betamethasone group a significant reduction in lesions diameter was evident only after the 5(th) day. No significant differences in VAS (p > 0.05) and the OHIP-14 (p > 0.05) between groups were found. CONCLUSION: No evidence of differences between the two compared interventions was found. REGISTRATION: Retrospective registration of this trial was conducted in ClinicalTrials.gov on September 30, 2016; trial registration number: NCT02920658. https://clinicaltrials.gov/ct2/show/NCT02920658?term=NAVS&draw=2&rank=4.